PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN MELALUI MOTIVASI KONSUMEN SEBAGAI VARIABLE INTERVENING PADA PRODUK SKINCARE DI SAMARINDA - Resty Meilia Nanda; Anastasia Natalia Sudarwati; Tisya Ayu Andriani (Jurnal GeoEkonomi, 2024)
In today's era, the development of social media is something that supports consumers in the motivation to shop for beauty store products. In addition, information and sources circulating among the public become one of the decision making in purchasing. This study aims to determine the influence of social media on purchasing decisions through consumer motivation on beauty store products. This study used quantitative methods. A total of 100 respondents were determined using purposive sampling. Data collection techniques through questionnaires and processed using partial least square. The results showed that social media has an influence on purchasing decisions, and consumer motivation has a significant effect on purchasing decisions for beauty store products.